Stem cell memory - Sherley, James (Henry Stewart Talks, 2007)
Defining stem cell memory, Deterministic asymmetric self-renewal evidence, Two classes of adult stem cell memory, The genetic fidelity problem, Chromosome segregation vs. co-segregation, Asymmetric self-renewal models, Biochemical control of asymmetric self-renewal, Potential molecular elements, ASRA gene signature discovery, Properties of H2A.Z
Updated at 2017/12/31